Formation of monument protection activities in Soviet Belarus in the years of «thaw» (1953–1968) - Huzhalouski, Alexander A. (Journal of the Belarusian State University. History, 2021)
The author analyses the change in state policy, as well as the revival of public initiative in the field of protection of cultural monuments, as a result of the liberalisation of social and political life in Soviet Belarus during the «thaw». Public speeches of cultural figures, scientists, teachers, journalists served as an impetus for the actions of republican and local state bodies, who decided the fate of national heritage objects. The state officials and society representatives efforts undertaken during the period under review resulted with the creation of the Belarusian voluntary society for the protection of historical and cultural monuments (1966), the State inspectorate for the protection of historical, artistic, architectural and archaeological monuments (1967), as well as with the adoption of «On the protection of cultural monuments» law (1969).